SEKAHA TERUNA DALAM LANSKAP LINGUISTIK BALI: ANALISIS SOSIO-ONOMASTIKA TERHADAP POLA PENAMAAN DAN IDENTITAS BUDAYA - Ediwan, I Nyoman Tri (Prosiding Seminar Nasional Bahasa Ibu, 2025)
Bali possesses a rich linguistic heritage reflected in the linguistic landscape of public spaces, one of which is the nameplates of traditional youth organizations known as Sekaha Teruna under the banjar adat system. This study analyzes the language use in Sekaha Teruna nameplates through the perspectives of Linguistic Landscape (LL) and socio-onomastics. The LL approach examines how language, symbols, and linguistic signs displayed in public spaces reflect the social, cultural, and ideological dynamics of the community. Meanwhile, the onomastic approach explores the origins, meanings, and naming patterns of Sekaha Teruna in relation to social identity and local values. Data were collected through direct observations of Sekaha Teruna nameplates in various areas of Bali, both in urban and rural settings, using photographic documentation and interviews with traditional leaders and community members. The analysis reveals that the naming of Sekaha Teruna is dynamic and influenced by various factors, such as religious values, local history, and social aspirations. Most Sekaha Teruna names incorporate loanwords from Sanskrit, which have been integrated into Old Javanese and reflect the Hindu-Balinese social identity. Additionally, the use of acronyms and metaphors in naming patterns highlights the community’s creativity in representing values and aspirations for younger generations. By integrating LL and onomastic perspectives, this study reveals that Sekaha Teruna nameplates serve not only as organizational identity markers but also as representations of ideology and cultural values that continue to be preserved by Bali’s traditional communities.